EFFECT OF VITAMIN C AND E SUPPLEMENTATION TO TRIS EGG YOLK EXTENDER ON CANINE EPIDIDYMAL SPERMATOZOA FOLLOWING CRYOPRESERVATION - M. Waqas; F. L Lodhi; R. Kausar; S. Umer; H. Jamil (Pakistan Journal of Agriculture, Agricultural Engineering & Veterinary Sciences)
Cryopreservation of spermatozoa is a method of choice to preserve genetic potential of fertile proven dogs when they die unexpectedly or fail to ejaculate. In this scenario, present study was designed to monitor the individual and combined effects of supplementation of two antioxidants (Vitamin E 0.3mM and Vitamin C 0.90mg) to freezing extender tris egg yolk (TEY) via cryopreservation on the canine epididymal sperm quality parameters. For this purpose, testes were collected from 20 healthy dogs and cauda epididymal semen samples were extracted after dissection. The collected samples were evaluated for sperm motility and viability after that extended in TEY extender. The extended semen samples were loaded in 0.25ml straws and plunged into liquid nitrogen after holding the straws in liquid nitrogen vapors for two minutes then plunged into LN2. Then the frozen samples were thawed for 15 seconds at 50°C and subjected to post-thaw evaluation through CASA. The data were analyzed using one-way ANOVA under CRD and means were compared using Tukey's test. Results revealed that the post-thaw semen parameters progressive sperm motility, viability, plasma membrane integrity and motion kinetics straight-line velocity, curvilinear velocity increased significantly (P< 0.05) in the TEY with vitamin C and vitamin E groups, except for amplitude of lateral head displacement which was significantly decreased (P< 0.05), compared to control group. Based on the results of this study, it was concluded that supplementation of vitamin C and E alone or in combination with TEY extender significantly (P< 0.05) improved canine epididymal sperm quality parameters following cryopreservation.